AN EVALUATION OF THE ATTITUDE OF ISTANBUL’S YOUTH SERVİCES AND SPORT DIRECTORATE EMPLOYEES TOWARDS FEMALE MANAGERS - Mustafa Zahit SERARSLAN (Fırat University, 2019)
The aim of this study is formulated upon the attitude of the employees of Istanbul’s Youth Services and Sport Directorate towards female managers taking into account some demographic variables such as rank within the organization and length of service of employees. The population of the study comprised of the 380 employees of Istanbul’s Youth Services and Sport Directorate; 297 were male and 83 female. In order to determine attitudes towards female managers, a survey consisting of 19 items was carried out on 140 of the employees of Istanbul’s Youth Services and Sport Directorate; 104 male and 36 female. The scale consisting of 19 questions which was developed by Negiz and Yemen in their 2011 study entitled “The Attitude of Female Managers and Employees” was implemented. The validity of the scale was measured using the alpha method and was found to be 0,93. The data was analysed in an electronic environment. According to the results of the noramlity test, the data revealed normal distribution. Due to the fact that the descriptive research design of the research data used contained a characterisitic of a non-parametric nature, the Kuruskal-Wallis Test was analaysed at a significance level of 0,05. Results reveal that employees generally viewed the competency of female managers to be substandard or at a low level. There was a meaningful difference between the views of male and female employees on the subject of female managers’ competency. Female employees viewed female managers to be more capable in contrast to male employees. Aside from this, variables such as educational attianment of employees such as their age, title and length of service did not reveal a difference in the levels of attitude towards working with female managers